A study of a distal lesion of substantia nigra neurons in the rat brain : a model for Parkinsonism - Van der Spuy, Gian D (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Biochemistry)) -- University of Stellenbosch, 1991.